Formaç\~ao continuada dos professores e a política nacional de educaç\~ao digital - Lenita Turchi; Ana Luiza Machado de Codes; Herton Ellery Araújo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This study aims to contribute to the debate and regulation of the Brazilian National Digital Educational Policy (PNED) - Law No. 14.533/2023. It focuses on the articles that advocate the need to build teachers capacity to deal with digital technologies and strategies to promote a continuous learning environment. The study examines teachers' perception and evaluation of their knowledge in the use of information and communication technologies (ICT), in educational activities during 2021. Its draws a picture of teachers' perceptions of their knowledge and competencies to deal with digital technologies and points out the challenges faced by them. Among the finding, of this study, it is worth to mention that the majority of the teachers' respondents have attended courses and or received training for pedagogical use of digital technologies. In addition, the courses or on the job training were offered by governmental agencies. However, the nature of the training and the quality as well as attendance to them were very heterogenous reflecting the economic and social inequalities found among Brazilian regions. The inequality in terms of access of digital devices and connection, among public school, indicates that issues regarding digital education and teachers' capability building, have little or none integration with the national education policy. This study recommends that the digital education law should be integrated to the 2024-2034 National Education Policy.
Keywords: I24; 330; digital education; teachers; capacity building